2007
DOI: 10.1103/physrevlett.98.113401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Enhancement in Cobalt-Manganese Alloy Clusters

Abstract: Magnetic moments of Co(N)Mn(M) and Co(N)V(M) clusters (N < or = 60; M < or = N/3) are measured in molecular beams using the Stern-Gerlach deflection method. Surprisingly, the per atom average moments of Co(N)Mn(M) clusters are found to increase with Mn concentration, in contrast to bulk CoMn. The enhancement with Mn doping is found to be independent of cluster size and composition in the size range studied. Meanwhile, Co(N)V(M) clusters show reduction of average moments with increasing V doping, consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 26 publications
8
51
0
Order By: Relevance
“…They have also found that the total enhancement in the magnetic moment to be 1.7 µ B /Mn-substitution, and is independent of the cluster size n and composition, which is justified by the virtual bond state model. 31 The present calculation is in good agreement and we find this enhancement to be 2 µ B /Mn-substitution (Tables I-IV) as long as cluster is ferromagnetic (Co-rich). …”
Section: Comparison Of Magnetic Moment With Stern-gerlach Experimentssupporting
confidence: 83%
See 2 more Smart Citations
“…They have also found that the total enhancement in the magnetic moment to be 1.7 µ B /Mn-substitution, and is independent of the cluster size n and composition, which is justified by the virtual bond state model. 31 The present calculation is in good agreement and we find this enhancement to be 2 µ B /Mn-substitution (Tables I-IV) as long as cluster is ferromagnetic (Co-rich). …”
Section: Comparison Of Magnetic Moment With Stern-gerlach Experimentssupporting
confidence: 83%
“…More recently Yin et al have measured the magnetic moments of Mn x Co y (y ≤60; x≤y/3) clusters and found an increase in peratom magnetic moment for Co-rich Mn x Co y cluster with increasing Mn concentration. 31 This enhancement in moment due to Mn doping is independent of cluster size and composition. On the other hand, for Mn-rich clusters, for more than 40% Mn concentration, the average magnetic moment of Mn x Co y cluster decreases with increasing Mn concentration.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, the magnetic moments of the Co n Mn m and Co n V m clusters were measured in molecular beams with the Stern-Gerlach deflection method. 7 And it was found that, for the Co-rich Co n Mn m clusters, the average magnetic moments increase with the increasing Mn concentration, which is in contrast to bulk CoMn. However, for the Co n V m clusters, the average magnetic moments decrease with the increasing V dopant.…”
Section: Introductionmentioning
confidence: 98%
“…Besides, the heterogeneous magnetic structures offer opportunities for clusterassembled materials with new functions for magnetic recording and medical applications [1,2]. To date, a few studies have been made on the structural and magnetic properties of cobalt-based bimetallic TM clusters [3][4][5][6][7][8][9][10][11]. Experimentally, magnetic deflection study of Co n Bi m suggested that the clusters adopt segregated structures with ferromagnetic Co n "cores" surrounded by the Bi atom shell [3].…”
Section: Introductionmentioning
confidence: 99%